Influence of Natural Fibers on the Performance of Hot Mix Asphalt for the Wearing Course of Pavement - Mahmood, Omar T.; Ahmed, Sheelan A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
Cracking in the flexible pavement is a serious problem that reduces the service life of the roads pavement unless they are treated with great care. Since flexible pavement is very weaker in tension than in compression, it is usually necessary to consider the tensile stresses and some type of additives to improve asphaltpavement performance, and one of the most effective ways of improving asphalt pavement performance is to reinforce asphalt mixtures by incorporating natural fibers. The main objective of this study is to use palm fiber, which is locally available, in hot mix asphalt mixtures. To achieve this objective, the Marshall test and indirect tensile strength test were conducted on four asphalt mixtures with different types of natural fibers (Coconut, Corn, Palm, and Sisal), added in varying percentages 0.1, 0.2, 0.3, 0.4, and 0.5% and different lengths of fiber 0.5, 1, 1.5, and 2 cm. Based on the analyzed results, it can be concluded that the use of palm fiber increased the Marshall stability by 20% as compared with the conventional mixture and raised up the retained tensile strength ratio up to 92%. Finally, the use of 0.2% content of natural fiber at 1.5 cm length gave a better performance for the mixtures.